The Role of Electronic Medical Records as a Professional Communication Tool for Caregivers at Nyi Ageng Serang Hospital: Peran Rekam Medis Elektronik sebagai Alat Komunikasi Profesional Pemberi Asuhan di RSUD Nyi Ageng Serang - Nurdiyansyah, Andi Karisma; Wuryanto, Sis; Asgiani, Piping; Setiawan, Fendi (Procedia of Engineering and Life Science, 2025)
To improve the quality and efficiency of health services in hospitals, there needs to be good communication from care professionals working at the service facility. Communication between care-giving professionals can be done by data communication through Electronic Medical Records (RME). RSUD Nyi Ageng Serang has implemented an outpatient RME to support patient care. However, the existing application has not been optimally utilised. The aim was to determine the role of RME as a communication tool between care professionals at Nyi Ageng Serang Hospital. The type of research used was descriptive qualitative research with a cross sectional design. This study used observation and focused group discussion (FGD) methods for data collection. The subject of this research is professional caregivers in outpatient installations while the object is RME. The data analysis technique used was qualitative data analysis technique starting with data reduction, data presentation, and continued with conclusion drawing. The role of electronic medical records in the implementation of interprofessional communication and collaboration is as a means of communication, especially where every finding and opinion of health professionals by care-giving professionals is poured and put together in electronic medical records, the findings of the medical history and actions given to patients and documented in writing or recorded. However, all of these provide benefits such as more complete RM content, business and communication efficiency, strategic benefits, and easy access to information. The completeness of patient data documentation in the RME at Nyi Ageng Serang Hospital can be improved through strengthening supporting regulations for documentation, training on the completeness of patient data filling for PPAs, adding features to check the completeness of documentation and designing a reward and punishment system for PPAs in terms of completeness of documentation in the RME. The addition of optional features to determine the diagnosis of disease by adding a list of disease diagnoses based on ICD-10 to the RME system database which makes writing a patient's medical diagnosis more concise and standardised and writing the main diagnosis is only written one diagnosis.